(3OjhGf GHf GdaGQVs - (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s
(3ChdgG (B:s
(3bGd Ydi SHW GdTjN GHf GdaGQV fXQJ aj fSN ef OjhGf TjNfG bOS Gddg SQg aQCjJ GdfSGN LgdhG HYV cdGeg heG YQahg, hGTJHg Ydjge TF ef LfGSg aUMahg s
(3BNQgG (B:s
(3pUrd YGTbG gLQ GdcQi hLaG GdhQi hQCi GdeMHI Ojfg aJOjfG Ke gPG GdOjhGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B58 - (3U(B147s
(3fSNI KGdKIs
(3hHYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B216s
Keywords: (3GdCOHs